Latent Constructs in Psychosocial Factors Associated with Cardiovascular Disease: An Examination by Race and Sex - Clark, Cari J.; Henderson, Kimberly M.; Mendes de Leon, Carlos F.; Guo, Hongfei; Lunos, Scott; Evans, Denis A.; Everson-Rose, Susan A. (Frontiers in Psychiatry, 2012)
Introduction: This study examines race and sex differences in the latent structure of a wide range of psychosocial measures and whether the identified factors are related to self-reported history of coronary heart disease (CHD). Materials and Methods : The sample included 4,128 participants of the Chicago Health and Aging Project. Exploratory factor analysis (EFA) with oblique geomin rotation was used to identify latent factors among 10 psychosocial measures. Multi-group comparisons of the EFA model were conducted using exploratory structural equation modeling. Measurement invariance was defined by a difference in the CFI of less than 0.01. For invariant factor(s), a factor-based scale score was created. Differences in mean scale scores across race-sex subgroups were tested with analysis of variance and Sheffe’s test. Logistic regression was used to test the relationship between the factor score(s) and CHD adjusting for relevant confounders. Effect modification of the relationship by race-sex subgroup was tested. Results : A two-factor model fit the data well (CFI=0.986; TLI=0.969; RMSEA=0.039). Factor I was comprised of depressive symptoms, neuroticism, perceived stress, and low life satisfaction. Factor II was comprised of social engagement, spirituality, social networks, and extraversion. Only Factor I, renamed Distress, showed measurement invariance across subgroups, although the level of Distress varied by race and sex. Distress was significantly related to report of CHD (odds ratio: 1.37; p-value < 0.0001). This effect did not differ by race or sex (interaction p-value=0.43). Conclusions: This study found two underlying latent constructs among a large range of psychosocial variables, but only one, Distress, was validly measured across race-sex subgroups. This construct was also robustly related to prevalent CHD, highlighting the potential importance of latent constructs as predictors of cardiovascular disease.